Reducibility of the Moduli Space of Stable Rank 2 Reflexive Sheaves with Chern Classes c1 = −1, c2 = 4, c3 = 2 on Projective Space P³ - A. S. Tikhomirov; M. A. Zavodchikov (Моделирование и анализ информационных систем, 2014)
We prove the reducibility of the moduli space MrefP³(2; −1, 4, 2) of stable rank 2 re- flexive sheaves with Chern classes c₁ = −1, c₂ = 4, c₃ = 2 on projective space P³. This gives the first example of a reducible space in the series of moduli spaces of stable rank 2 reflexive sheaves with Chern classes c₁= −1, c₂ = 4, c₃ = 2m, m = 1, 2, 3, 4, 5, 6, 8. We find two components of the expected dimension 27 of this space and give their geometric description via the Serre construction.